Different Acupuncture Treatments for Myofascial Pain Syndrome in Neck or Shoulder: A Network Meta-Analysis Based on Randomized Controlled Trials - Wang T; Gu Y; Li Y; Chen J; Zeng L (Journal of Pain Research)
Tian Wang,1 Yandong Gu,1 Yao Li,1 Jing Chen,2 Lirong Zeng3 1Tianjin Hospital, Tianjin, 300211, People’s Republic of China; 2College of Medical Imaging Laboratory and Rehabilitation, Xiangnan University, Chenzhou, Hunan, 423000, People’s Republic of China; 3Department of Rehabilitation Medicine, The First People’s Hospital of Chenzhou (The First Affiliated Hospital of Xiangnan University), Chenzhou, Hunan, 423000, People’s Republic of ChinaCorrespondence: Jing Chen, College of Medical Imaging Laboratory and Rehabilitation, Xiangnan University, No. 25, West Renmin Road, BeiHu District, Chenzhou, Hunan Province, 42300, People’s Republic of China, Tel +86 18075537186, Email chenjing010@126.com Lirong Zeng, Department of Rehabilitation Medicine, The First People’s Hospital of Chenzhou (The First Affiliated Hospital of Xiangnan University), No.102 Luojiajing, Beihu District, Chenzhou, Hunan Province, 42300, People’s Republic of China, Tel +86 18075530126, Email 381126564@qq.comBackground: Myofascial Pain Syndrome (MPS) is a prevalent musculoskeletal condition. Acupuncture therapy demonstrates significant advantages due to its unique mechanism of action. However, there are notable discrepancies in the evidence levels among various acupuncture therapies, and direct comparative data between different treatments remain scarce.Methods: Randomized controlled trials (RCTs) investigating acupuncture therapy for MPS in Neck or shoulder were systematically retrieved from CNKI, Wanfang, VIP, CBM, PubMed, EMbase, Cochrane Library, and Web of Science up to April 30, 2025. Network Meta-analysis was conducted using Stata 16.0.Results: This study included 29 RCTs, involving a total of 2424 patients. Thirteen types of interventions were evaluated in the experimental groups: Fu’s subcutaneous needling, Internal heat acupuncture, Electroacupuncture, Round-point needle, Needle knife, Moxibustion, Sunken cord, Acupoint injection, Conventional acupuncture + Moxibustion, Conventional acupuncture + Bloodletting, Conventional acupuncture + Traditional Chinese Medicine (TCM), Conventional acupuncture + Tuina, and Conventional acupuncture + Exercise. Regarding the Visual Analog Scale (VAS) scores:The top three therapies based on the Surface Under the Cumulative Ranking Curve (SUCRA) values were Moxibustion (0.84), Internal heat acupuncture (0.84), and Conventional acupuncture + Moxibustion (0.79). In terms of efficacy, based on the SUCRA rankings for both outcome indicators, Internal heat acupuncture was identified as having the best overall effect.Conclusion: Based on the findings of this study, multiple acupuncture methods exhibit significant advantages over conventional acupuncture. Comprehensive analysis indicates that Internal heat acupuncture has the most favorable therapeutic effect.Keywords: myofascial pain syndromes, acupuncture, visual analog scale, network meta-analysis